The effect of biological pre-treatments on germination, growth and physiological indices of Fenugreek (Trigonella foenum-graecum L.) seedling under natural salinity stress - mousavi seyyed mehdi; Heshmat Omidi; seyyed esmaeil mousavi (علوم و فناوری بذر ایران, 2022)
To study of the effect of biological pre-treatments on germination and growth of Fenugreek (Trigonella foenum-graecum L.) seedling under natural salinity stress, a factorial experiment in a completely randomized design was conducted in three replications. Experimental treatments were biological pre-treated at four levels (control, inoculation with Azoto bio-fertilizer, inoculation with Phosphate bio-fertilizer, inoculation with both bio-fertilizers) and natural salinity (salt of Qom Lake) at five levels (zero, 3, 6, 9 and 12 dS/m).The results showed that increasing of salinity levels led to increasing of mean germination time and using of bio-fertilizer treatments and combination treatment caused this index show 22 percentages reduction at highest level of salinity compared to control treatment at same level of salinity. Salinity reduced the germination coefficient and the highest amount of this index (74.3) obtained at 3 dS/m level of salinity that compared to control treatment and at the same level of salinity showed 89 percentages increasing. Salinity reduced total chlorophyll and using of biological treatments caused amount of total chlorophyll at zero level of salinity show 155 percentages increasing compared to control treatment and at the same level of salinity. With increasing of salinity level increased soluble protein and combination treatment increased this index 12 percentages at the highest level of salinity compared to control. Under stress, plants face with oxidative stress and to confront of that use antioxidant enzymes. In this experiment, the using of biological treatments by raising of the production of antioxidant enzymes caused the reduction of salinity effects.